The association between bone mineral density and periodontitis in Korean adults (KNHANES 2008–2010). (1st October 2013) - Kim, J‐W; Kong, K‐A; Kim, H‐Y; Lee, H‐S; Kim, S‐J; Lee, S‐H; Sim, K‐W; Kim, M‐R; Lee, J‐H
<x xml:space="preserve">Abstract</x> Objectives This study investigated the association between bone mineral density (BMD) and periodontitis in a representative sample of Korean adults. Material and Methods Of 36 188 individuals who participated in the Korea National Health and Nutrition Examination Survey in 2008, 2009, and 2010, 9977 participants aged ≥40 years were included in this cross‐sectional study. The associations of BMD of lumbar spine, total femur, and femoral neck with periodontitis were investigated using logistic regression analysis. Additionally, dose–response relationships with BMD divided into quintiles and the association between osteoporosis and periodontitis were investigated. Results With the set of Community Periodontal Index (CPI) ≥ 3 as a dependent variable, logistic regression analysis revealed that a decrease of BMD was significantly associated with higher odds of periodontitis [range of adjusted odds ratios (AORs); 1.15–1.20, P < 0.001 for all BMD sites]. Similarly, these associations were also found in the CPI 4 model. With regard to dose–response relations, the lower the BMD quintile, the higher the AORs appeared with statistical significance in the CPI ≥ 3 model. (P for trend < 0.001) Participants with osteoporosis had 2.26 and 1.91 times higher odds for CPI ≥ 3 and CPI 4, respectively, than those with normal BMD, indicating a significant association between the two diseases. Conclusions Our results suggest that BMD is significantly associated with periodontitis.